A performance measurement framework for Global Virtual Teams (GVTs) in global IT projects - Gheni, Ali Yahya; Jusoh, Yusmadi Yah; A. Jabar, Marzanah; Mohd Ali, Norhayati (American-Eurasian Network for Scientific Information, 2016)
In spite of the increasing prevalence of global virtual teams (GVTs), It should be noted that in spite of the advantages of technology provides, most of global IT projects tend to face problems and risks, and great deal of such projects fail to reach all their objectives. According to the literature review we found that there is a lack of communication within global virtual teams in global IT projects and this problem affect the global IT project performance and leads to global IT project failure. So there is a need to develop a framework to measure the performance for global virtual teams in global IT projects. Early stage and before developing the instrument and conducting the pilot test, the researchers conducted a structured interview with 6 experts to validate the proposed framework. In conclusion, The validity and reliability of the instrument were tested through experts, typical respondents, and analyzed by SPSS 22. The results confirmed the validity of the proposed framework and the validity and reliability of the instrument.